2009
DOI: 10.1002/ccd.22257
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the prehospital ECG on door‐to‐balloon time in ST elevation myocardial infarction

Abstract: Utilizing the prehospital ECG as a tool to bypass ER triage significantly decreases D2B times in patients with STEMI. This technology has the potential to substantially expedite reperfusion therapy in patients with STEMI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
28
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(30 citation statements)
references
References 10 publications
0
28
2
Order By: Relevance
“…Several studies in the literature have shown improved reperfusion times in patients with STEMI when PH ECG is acquired. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] LeMay et al 11 instituted a citywide protocol in Ottawa for STEMI management. They included paramedic interpretation, activation, and direct patient transport to the city's cardiac care center rather than any of the city's 4 hospital EDs, with a median DTB of 69 minutes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several studies in the literature have shown improved reperfusion times in patients with STEMI when PH ECG is acquired. [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16] LeMay et al 11 instituted a citywide protocol in Ottawa for STEMI management. They included paramedic interpretation, activation, and direct patient transport to the city's cardiac care center rather than any of the city's 4 hospital EDs, with a median DTB of 69 minutes.…”
Section: Discussionmentioning
confidence: 99%
“…They included paramedic interpretation, activation, and direct patient transport to the city's cardiac care center rather than any of the city's 4 hospital EDs, with a median DTB of 69 minutes. Rao et al 15 published a report on a prehospital STEMI protocol using wireless transmission, in which the ED physician interpreted the ECG and activated the catheterization laboratory before patient arrival, and their median DTB was 60 minutes. Camp-Rogers et al 3 reported a mean DTB of 49 minutes when paramedics reviewed electronic ECG interpretations and activated the laboratory in the prehospital setting, but they did not bypass the ED for any patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) The accurate diagnosis of STEMI is critical for quick and efficient treatment [2][3][4] and 12-lead electrocardiography (ECG) transmission in the pre-hospital time period could contribute to reducing the door-to-balloon time. [5][6][7][8][9][10][11][12] However, few Japanese ambulances are currently equipped with an ECG transfer system. In Japan, the medical-related activities of emergency lifesaving technicians in the field is strictly controlled by the law.…”
Section: P Atients With St-segment Elevation Myocardial Infarctionmentioning
confidence: 99%
“…[2][3][4][5][6][7] However, efforts made only in hospitals are insuffi cient, and how quickly the prehospital information is used for preparation of emergent catheterization is very important. 2,8) Kitasato University Hospital has sent its Doctor Car to deal with cases of acute myocardial infarction.…”
mentioning
confidence: 99%